Analysis of Helichrysum oligocephalum DC. essential oil - N. Ghassemi-Dehkordi; M. Sadeghi; M.R. Kaviani; B. Zolfaghari (Iranian Society of Pharmacognosy, 2015)
Background and objectives: Helichrysum oligocephalum DC. (Compositae)  is an endemic plant in Iran that has been recommended by Iranian traditional and folk medicine practitioners for gastrointestinal complaints. The plant is rich in essential oil and in the present investigation, the volatile composition of the species has been determined. Methods: The light yellow essential oil from the aerial parts of the plant was prepared according to the method which was recommended in British Pharmacopoeia by using hydrodistillation. The chemical composition of the oil was investigated by gas chromatography mass spectroscopy (GC/MS). Results: Thirty-seven compounds were identified; among them β-caryophyllene, α-humulene and epimanoyl oxide were dominant. Sesquiterpenoids were the most dominant compounds in the essential oil while monoterpenoides, fatty acids and diterpenoides were found to be less. These outcomes are a little bit different from what has been reported before. Conclusion: The differences between the results of the present study with previous works could be due to the diversity of variety, polymorphism, stage of plant growth and environmental factors.